Labiolingual and mesiodistal positioning of maxillary permanent incisors during the eruption process - Cuoghi, Osmar Aparecido [UNESP] (MRE Press, 2000)
This study aimed to establish radiographical parameters concerning the tipping, the labiolingual positioning and the angulation of the maxillary permanent incisors in the mixed dentition. Three groups of 20 cephalograms and 20 orthopantomographic radiographs taken from children aging from 7 to 12 years old, with normal occlusion were compared. The Group I presented only the eruption of the central permanent incisors, the Group II presented both the central and lateral permanent incisors and the Group III presented central, lateral incisors and permanent canine teeth. The tipping and the labiolingual positioning were measured, respectively, using U1/PP and U1↔AVERT. Mesiodistally, the angles between the teeth axis and the line that touched the lower border of the orbit in the orthopantomographic radiographs were measured. The mean values of tipping, labiolingual positioning and angulation of the central and lateral incisors obtained from Groups I, II and III were respectively 112°, 1.2mm, 90.4° and 91.7°; 112°, 2.6mm, 89.5° and 96.8° and. 114°, 2.7mm, 87.4° and 92.6°. The tipping levels were similar for all groups, the mean values of the labiolingual positioning were significantly different at 5% when Group I was compared to both Groups II and III. And the mean values of the angulation were significantly different 5% for the central incisors between Groups I and III, and at 1% for the lateral incisors between Groups I and II, and, II and III.